Interactive effect of prepregnancy overweight/obesity and GDM history on prevalence of GDM in biparous women - Xu, Xia; Huang, Feipeng; Guo, Yanni; Zheng, Lianghui; Yan, Jianying (Frontiers in Endocrinology, 2023)
Background: Pre-pregnancy overweight/obesity (OWO) and GDM history may increase the prevalence of GDM in parous women, but little is known about their potential combined effect on prevalence of GDM in biparous women. Objective: To explore the interactive effect of pre-pregnancy overweight /obesity (OWO) and GDM history on the prevalence of GDM in biparous women. Methods: A retrospective study including 16, 282 second-birth women who delivered a single neonate at a gestation age of ≧28 weeks twice was performed. Logistic regression were used to assess the independent and multiplicative interactions of pre-pregnancy overweight/obesity (OWO) , GDM history and risk of GDM in biparous women. Additive interactions were calculated using an Excel sheet which was made by Anderson to calculate relative excess risk. Results: A total of 14,998 participants was included in this study. Both pre-pregnancy OWO and GDM history were independently associated with an increased risk of GDM in biparous women ( OR=19.225, 95% CI=17.106 , 21.607 and OR=6.826 , 95% CI=6.085, 7.656, respectively). The coexistence of pre-pregnancy OWO and GDM history was associated with GDM, with an adjusted OR of 1.754 (95% CI, 1.625, 1.909) compared to pregnant women without either condition. The additive interaction between prepregnancy OWO and IMH was found to be no significant with regard to GDM in biparous women. Conclusions: Pre-pregnancy OWO and GDM history both increase the risk of GDM in biparous women and has multiplicative interaction but not additive interaction.